Clinical And Neurological Immunological Features of The Vertebrobasilar System Against the Background of Vertebral Artery Syndrome (Eurasian Medical Research Periodical, 2022)
For neurologists, it is important to understand that depression can be organic in nature, associated with local or diffuse brain damage. In such cases, emotional disorders are included in the structure of the general neurological deficit associated with brain damage. Circulatory disorders in the vertebrobasilar system (VBS) have attracted the attention of specialists for a long time. They belong to severe and frequent variants of cerebrovascular pathology. According to the Department of Epidemiology and Demography of the WHO, hemodynamic disorders in the vessels of the vertebrobasilar basin account for more than 30% of all cerebrovascular diseases. About 70% of transient cerebrovascular accidents are due to circulatory disorders in the vertebrobasilar system. The article presents a brief review of the literature data on the problem of circulatory failure in the vertebrobasilar system